Review about Manuel de Puelles Benítez (coord.): School failure in the state of the autonomous communities - Editorial, Equipo (Avances en Supervisión Educativa, 2012)
Título: EL FRACASO ESCOLAR EN EL ESTADO DE LAS AUTONOMÍAS: DEL FRACASO AL ÉXITO ESCOLARAutor: MANUEL DE PUELLES BENÍTEZ (COORD.)Editorial: Wolters Kluwer.Madrid, 2012.